Adrenal adenoma secreting 17-hydroxyprogesterone mimicking non-classical 21-hydroxylase deficiency - Woźniak, Beata; Leszczyńska, Dorota; Szatko, Alicja; Nowak, Karolina; Samsel, Radosław; Siejka, Anna; Papierska, Lucyna; Zgliczyński, Wojciech; Falhammar, Henrik; Glinicki, Piotr (Frontiers in Endocrinology, 2024)
In adrenal steroidogenesis, 17-hydroxyprogesterone (17-OHP) is a substrate for 21-hydroxylase, one of the crucial enzymes of the cortisol and aldosterone biosynthesis pathway. Thus, measurement serum 17-OHP concentration is used when the diagnosis of congenital adrenal hyperplasia (CAH) due to 21hydroxylase deficiency is suspected. In the classic 21-hydroxylase deficiency, randomly timed measurements of 17-OHP are generally significantly elevated using different immunoassays. In the non-classic form of CAH (NC-CAH), the activity of 21-hydroxylase is less decreased, therefore the measurements of 17-OHP after ACTH stimulation test are usually required for diagnosis. Nonetheless, elevated 17-OHP concentration may also origin from adrenal tumors or ovarian neoplasms as a result of defects in steroidogenesis with an accumulation of steroids precursors. The presented cases and the literature review draw attention to the occurrence of rare causes of benign adrenal adenomas with steroidogenesis defects which may lead to a misdiagnosis of CAH.